FOSTERING OF ENTREPRENEURSHIP CHARACTER OF STUDENT IN THE FACE OF THE ASEAN ECONOMIC COMMUNITY - Susan Fitriasari, Mimin Radiyah Sapriya (Jurnal Civicus, 2016)
Education is one of the efforts to solve the problems in Indonesia, one of them in order to answer the challenges of the global era, namely the ASEAN Economic Community. The main concept of the AEC is to create ASEAN as a single market. Himpunan Pengusaha Muda Indonesia of Indonesia University of Education (HIPMI UPI) as a student organization that has a vision student print that has the character of entrepreneurship by conducting entrepreneurial character building. The approach and method that used are a qualitative approach and descriptive method. The collection of data obtained through interview, observation and documentation. Subject of this research are an adviser of HIPMI UPI, commitee of HIPMI UPI, members of HIPMI UPI and an entrepreneurship lecturers of UPI. The results showed that: 1) the process of fostering the entrepreneurial character of students is implemented through program of HIPMI UPI, starting with the recruitment of new members until the grouping of member businesses so as to facilitate to know their business conditions; 2) priorities division between academic, organizations and entrepreneurs make many members were not consistent in running their business; the efforts that conducted is the personal approach to members whose conducted by commitee or executive of HIPMI UPI.Keywords: Enterpreneurship, Civic Education, Economic Civic